A Systematic Literature Review on the Integration of Spirituality and Religiosity in Shaping Managerial Ethics and Accounting Disclosure Quality - Said, Saida; Syarifuddin, Syarifuddin; Alimudin, Alimudin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study was designed to explore and synthesize the development of literature discussing the contribution of spirituality and religiosity in shaping managerial ethics and improving the quality of accounting disclosures. This study uses a Systematic Literature Review (SLR) approach following the PRISMA 2020 framework, in which 47 articles from a total of 483 relevant publications were rigorously selected for in-depth analysis. The main objectives of this analysis are to map the patterns of relationships formed, understand the mechanisms of influence at work, and identify areas that are still under-researched in the context of contemporary managerial morality. From the results of this systematic review, it was found that spirituality plays a significant role in fostering personal integrity, strengthening ethical awareness, and increasing the capacity for individual self-control. These dimensions directly encourage the rejection of manipulative practices in the financial reporting process. Conversely, religiosity plays a more effective social control system, which not only suppresses the practice of earnings management but also improves the accuracy and transparency of financial information disclosure, especially in environments with weaknesses in governance structures. This study also shows that the influence of spiritual and religious values is not simple or linear, but is influenced by a number of mediating and moderating factors. These factors include the level of understanding of religious teachings, the location of internal control (locus of control), individual technical competence, organizational culture, and the strength of the governance system including the existence and role of the Sharia Supervisory Board. Based on these findings, this study proposes an integrative conceptual model, which describes how spiritual and religious values can be transformed into financial reporting behavior that upholds ethics. In addition, this study also identifies various gaps in the literature, including the lack of studies that discuss spiritual experiences at the individual level (micro studies), the lack of a longitudinal approach in related research, and the limited context of studies that focus on developing countries. Therefore, this SLR makes a significant contribution to theory development by integrating two key moral elements in accounting research, as well as providing a clear direction for future research that focuses on ethics, spirituality, and sustainable governance practices.